Direct Detection of Streptococcus suis from Cerebrospinal Fluid, Positive Hemoculture, and Simultaneous Differentiation of Serotypes 1, 1/2, 2, and 14 within Single Reaction - Ingyin Shun Lae Thu; Khajornsak Tragoolpua; Sorasak Intorasoot; Usanee Anukool; Phadungkiat Khamnoi; Anusak Kerdsin; Chayada Sitthidet Tharinjaroen (Pathogens, 2021)
Streptococcus suis is an emerging zoonotic bacterium causing septicemia and meningitis in humans. Due to rapid disease progression, high mortality rate, and many underdiagnosed cases by time-consuming routine identification methods, alternative diagnostic testing is essential. Among 29 broadly accepted S. suis serotypes, serotypes 2 and 14 are high prevalent; however, many PCR assays showed an inability to differentiate serotype 2 from 1/2, and 1 from 14. In this study, we developed and validated a new multiplex PCR assay that facilitates the identification of only the 29 true serotypes of S. suis and simultaneously differentiates serotypes 1, 1/2, 2, and 14 within a single reaction. Importantly, the multiplex PCR could detect S. suis directly from positive hemocultures and CSF. The results revealed high sensitivity, specificity, and 100% accuracy with almost perfect agreement (κ = 1.0) compared to culture and serotyping methods. Direct detection enables a decrease in overall diagnosis time, rapid and efficient treatment, reduced fatality rates, and proficient disease control. This multiplex PCR offers a rapid, easy, and cost-effective method that can be applied in a routine laboratory. Furthermore, it is promising for developing point-of-care testing (POCT) for S. suis detection in the future.